CONVERSION AND ITS MOST COMMON TYPES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article is dedicated to the study of one of the productive ways of word formation “conversion”. Different approaches to the study of conversion  such as synchronic and diachronic approaches are also discussed in the article.